Subsisting on boiled rice and pulse: understanding histories of famine, feast and migrant health, through the lens of Girmit-descendants* - Pritika Narayan; Roshika Deo; Thrishila Parshu Ram; Nikki Singh (Kōtuitui)
The repercussions of historical famines continue to impact on the health and wellbeing of ethnic minority groups in Aotearoa today, particularly for populations with histories of Girmit (indenture), such as Indo-Fijians. This paper provides critical insights on how decades of intergenerational famine exposure and colonial dietary conditions during the Girmit continue to influence the health outcomes of descendants even now, when the threat of famine is removed. We present original archival research to analyse the extent of mortality associated with nutritional deficits and draw attention to the caloric deficits experienced by developing babies in the womb and the related high mortality during early infancy, throughout the Girmit era. We contextualise the lasting health impacts through a literature review of the intergenerational health impacts of famines from across the globe. We argue that evolving perspectives of migrant health disparities must also consider the intersections of history, colonisation, intergenerational famine and culture, in health interventions for current generations and we advocate for novel approaches in addressing health inequities for ethnic communities.